2006
DOI: 10.1093/jnci/djj105
|View full text |Cite
|
Sign up to set email alerts
|

Specific Peptide Ligand for Grb7 Signal Transduction Protein and Pancreatic Cancer Metastasis

Abstract: The Grb7 peptide inhibitor appears to be a promising molecularly targeted therapeutic agent against metastatic pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
132
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(138 citation statements)
references
References 35 publications
5
132
1
Order By: Relevance
“…We have shown previously that the G7-18NATE peptide inhibits the association of Grb7 with the ErbB family of tyrosine kinases (Pero et al, 2002) and focal adhesion kinase (Tanaka et al, 2006). The signal transduction pathway for Grb7 has not been identified clearly.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…We have shown previously that the G7-18NATE peptide inhibits the association of Grb7 with the ErbB family of tyrosine kinases (Pero et al, 2002) and focal adhesion kinase (Tanaka et al, 2006). The signal transduction pathway for Grb7 has not been identified clearly.…”
Section: Discussionmentioning
confidence: 97%
“…Combining chemotherapy with molecules, such as our Grb7 peptide, may have great potential at effectively killing the cancer cells and minimising toxicity. In our recent study we have shown that the Grb7 peptide inhibitor had low toxicity in mice (Tanaka et al, 2006). In addition, this peptide is non-phosphorylated, which may have an advantage of stability of other SH2 targeting peptides that possess a highly charged phosphate group.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this clinical study, protein expression of Grb7 was not significantly correlated with tumor size. It was reported that the Grb7 peptide inhibitor significantly attenuated cell migration in vitro and peritoneal metastasis in a mouse model of pancreatic cancer cells, but the proliferation of pancreatic cells treated with the Grb7 peptide inhibitor was not significantly different from that of untreated cells (20). These data suggested that Grb7 protein played an important role in cell invasion of HCC cells, but might not contribute to cell proliferation.…”
Section: Discussionmentioning
confidence: 84%